2013
DOI: 10.1186/ar4379
|View full text |Cite
|
Sign up to set email alerts
|

A complex interaction between Wnt signaling and TNF-α in nucleus pulposus cells

Abstract: IntroductionIncreased expression of the proinflammatory cytokine TNF-α in intervertebral discs (IVDs) leads to inflammation, which results in progressive IVD degeneration. We have previously reported that activation of Wnt-β-catenin (hereafter called Wnt) signaling suppresses the proliferation of nucleus pulposus cells and induces cell senescence, suggesting that Wnt signaling triggers the process of degeneration of the IVD. However, it is not known whether cross talk between TNF-α and Wnt signaling plays a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
62
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 42 publications
8
62
1
Order By: Relevance
“…Previous studies have analyzed the Wnt signaling pathway in nuclear pulposus cells and reported that activation of the Wnt signaling pathway inhibits the proliferation of nuclear pulposus cells and induces cell senescence, revealing that the Wnt signaling pathway promotes the progression of degeneration of intervertebral discs [36-38]. Largely consistent with our study, Hiyama et al reported that the Wnt signaling pathway modulates TNF-α, and the Wnt signaling pathway and TNF-α form a positive-feedback loop in nuclear pulposus cells [14]. …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have analyzed the Wnt signaling pathway in nuclear pulposus cells and reported that activation of the Wnt signaling pathway inhibits the proliferation of nuclear pulposus cells and induces cell senescence, revealing that the Wnt signaling pathway promotes the progression of degeneration of intervertebral discs [36-38]. Largely consistent with our study, Hiyama et al reported that the Wnt signaling pathway modulates TNF-α, and the Wnt signaling pathway and TNF-α form a positive-feedback loop in nuclear pulposus cells [14]. …”
Section: Discussionsupporting
confidence: 81%
“…TNF-α can activate the Wnt/β-catenin signaling pathway, which in turn inhibits adipocytic differentiation [13]. According to Akihiko Hiyama et al, activation of the Wnt signaling pathway increases TNF-α expression and may contribute to degeneration of nuclear pulposus cells, which suggests that blockade of Wnt signaling pathway has the potential to reduce the degeneration of nuclear pulposus cells [14]. However, the effect of the Wnt signaling pathway on the recovery of SCI still requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…We also identified LRP1, LRP2 and VLDLR, which act as receptors for activation of Wnt-signaling. Hiyama et al 42,. reported that the activation of Wnt signaling upregulates the pro-inflammatory cytokine TNF-α leading to disc degeneration.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies suggest that it might be associated with a number of factors, such as higher levels of pro-inflammatory and osteoclastogenic cytokines (17). Inflammatory cytokines are considered to play a major role in disease progression as, together with WNT signaling, they can form a positive feedback loop for modulation of bone remodeling (18). WNT signaling is considered to be an important pathway in bone formation and loss (19).…”
Section: Discussionmentioning
confidence: 99%